Fasting Activates Fatty Acid Oxidation to Enhance Intestinal Stem Cell Function during Homeostasis and Aging - Mihaylova, Maria M.; Cheng, Chia-Wei; Cao, Amanda Q.; Tripathi, Surya; Mana, Miyeko D.; Bauer-Rowe, Khristian E.; Abu-Remaileh, Monther; Clavain, Laura; Erdemir, Aysegul; Lewis, Caroline A.; Freinkman, Elizaveta; Dickey, Audrey S.; et al. (CELL PRESS, 2018)
Diet has a profound effect on tissue regeneration in diverse organisms, and low caloric states such as intermittent fasting have beneficial effects on organismal health and age-associated loss of tissue function. The role of adult stem and progenitor cells in responding to short-term fasting and whether such responses improve regeneration are not well studied. Here we show that a 24 hr fast augments intestinal stem cell (ISC) function in young and aged mice by inducing a fatty acid oxidation (FAO) program and that pharmacological activation of this program mimics many effects of fasting. Acute genetic disruption of Cpt1a, the rate-limiting enzyme in FAO, abrogates ISC-enhancing effects of fasting, but long-term Cpt1a deletion decreases ISC numbers and function, implicating a role for FAO in ISC maintenance. These findings highlight a role for FAO in mediating pro-regenerative effects of fasting in intestinal biology, and they may represent a viable strategy for enhancing intestinal regeneration.
Keywords: TISSUE HOMEOSTASIS; PPAR-DELTA; IN-VITRO; MTORC1; PROLIFERATION; REGENERATION; RESTRICTION; METABOLISM; MECHANISMS; EXPANSION; Cell Biology